(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: Evaluation of the results of percutaneous pinning of supracondylar fractures of the humerus in children at Hanoi Medical University Hospital. Subjects and Methods: Retrospective study describing 46 patients diagnosed with closed supracondylar humeral fractures, treated with closed reduction and percutaneous pin placement at Hanoi Medical University Hospital from October 2021 to June 2025. Results: The study included 46 patients, the average age was 6.67±2.73 (2-12); the male/female ratio was 1.3/1. The injured side with the left/right ratio: 25/21 cases. The average time from injury to surgery was 16.83±29.37 hours, in which the majority was <24 hours. The common cause of injury was living accidents (accounting for 89.13%), also encountered in sports accident and traffic accidents. Clinically, 100% of patients had symptoms of pain, limited elbow movement and no cases had vascular or nerve damage before surgery. Paraclinically, Gartland III grade supracondylar fractures were found in 34 cases, Gartland IV in 12 cases. Intraoperative treatment, there were 34 cases of 2 crossed pis, 11 cases of 3 crossed pins and only 1 case of 3 laterals pins. The average surgery time was 40.54 ± 11.36. The average treatment time was 2.43 ± 0.54 days (2-4). Intraoperative correction mostly achieved anatomical results, only 01 case had slight displacement. The results of functional recovery and aesthetics were quite good, accounting for 86.96%, there was no case of loss of elbow flexion and extension range > 15 degrees (according to Flynn). Conclusion: Closed reduction and percutaneous pinning provide good short-term results with small incisions, no blood loss and short hospital stay. This is an effective and safe option for the treatment of closed supracondylar humeral fractures in children.